(untitled) (Voice: A Biannual & Bilingual Journal, 2024)
We are delighted to present Volume 16, Number 2, December 2024, of Voice: A Biannual and Bilingual Journal, published by the Autar Dei Chaudharain Research Centre (ADCRC) at Mahendra Multiple Campus, Nepalgunj, Banke, Nepal. This edition showcases a rich and diverse collection of 14 articles, with ten written in English and four in Nepali. These articles span a wide array of disciplines, offering fresh perspectives and insights on contemporary issues across various fields. Among the highlights of this issue is an exploration of English as a Foreign Language (EFL) research practices, providing a comprehensive look into the methodologies and challenges faced in this area. An in-depth analysis of ecofeminism in Gaia offers a timely critique of environmental and gender issues, while an examination of Patanjali Ayurveda’s marketing strategies in Nepalgunj sheds light on local business practices and cultural integration. Furthermore, a study on the impact of microfinance on the socio-economic empowerment of women presents valuable findings that contribute to the broader conversation on development and gender equality in Nepal. In addition, research on the sustainable use of forest resources offers significant insights into environmental conservation, highlighting key challenges and strategies for effective resource management. Other noteworthy contributions include an analysis of Bhupi’s poetry, which delves into the cultural and literary significance of his work, as well as a study on child delivery practices, which provides a deeper understanding of health and cultural traditions in Nepal. Lastly, a fascinating exploration of matchmaking rituals adds a unique cultural dimension to this volume, shedding light on the evolving practices in Nepalese society. We extend our heartfelt gratitude to all the contributors, reviewers, and the editorial team for their tireless dedication in bringing this issue to fruition. Their commitment to academic excellence ensures the continued success of Voice as a platform for scholarly discourse. As we strive to foster a vibrant academic dialogue, we invite readers to engage with these thought provoking articles and contribute to the ongoing exchange of ideas in the academic community. We appreciate your contributions as a scholarly author and your continued support as a reader.